2010
DOI: 10.2118/121850-pa
|View full text |Cite
|
Sign up to set email alerts
|

How To Apply the Flow Velocity as a Design Criterion in RPM Treatments

Abstract: Summary The effect of water control using relative permeability modification (RPM) depends strongly on the well's flow rate because the permeability reduction decreases as the flow velocity increases. This will affect the volume and the properties of the injected RPM fluid. This paper discusses how the velocity-dependent permeability reduction can be accounted for in the job design. The approach is to introduce a velocity-dependent permeability reduction and to solve the Darcy law for non-Newton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…14. These results are in agreements with previous work (Stavland 2010) reporting that water based polymers will selectively reduce the water permeability and not the oil permeability. …”
Section: Core Flood With Oilsupporting
confidence: 93%
“…14. These results are in agreements with previous work (Stavland 2010) reporting that water based polymers will selectively reduce the water permeability and not the oil permeability. …”
Section: Core Flood With Oilsupporting
confidence: 93%
“…However, the efficiency of cross-linked polymers (gels) was found to vary with gas, oil, and water flow rates. In addition, the relative permeability modifier (RPM) performance decreases as the fluid flow rate increases, posing a risk of overestimating the water-cut reduction potential. Therefore, the influence of fluid flow rate needs to be included in the RPM design …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the influence of fluid flow rate needs to be included in the RPM design. 27 Furthermore, it was previously shown that the efficiency of a water shutoff treatment strongly depends on the gel quality (i.e., the gel's rigidity and stability). 28−31 Moreover, while there have been recent insights into the mechanism of gel deformation and the associated disproportionate permeability reduction (DPR), 25,32−35 further scientific understanding of gel behavior in relation to injection rates is required to guarantee successful gel placement in gas wells.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers use the term relative permeability modification (RPM) interchangeably, and relative permeability modifier for the treatment fluid. Sydansk and Seright (2007) have presented an extensive overview of the history and applications of DPR/RPM treatments in petroleum reservoirs, and Liang et al (1995), Stavland and Nilsson (2001), Stavland (2010), and Sydansk and Romero-Zerón (2011) discussed the DPR mechanisms.…”
Section: Introductionmentioning
confidence: 99%